Water-absorbing resin composition

The water-absorbing resin composition, with a potassium salt unit and controlled crosslinking, addresses the uneven absorption issue of potassium salt-based resins, achieving both rapid absorption and high capacity under load.

JP2024176182AInactive Publication Date: 2024-12-19SDP GLOBAL
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023094522
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-08
Publication Date
2024-12-19
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Potassium salt-based water-absorbing resins have a fast water absorption rate but struggle with achieving sufficient absorption under load due to partial surface crosslinking when surface cross-linking agents are used, leading to uneven distribution.

Method used

A water-absorbing resin composition is developed with a structural unit derived from a potassium salt of a water-soluble unsaturated monocarboxylic acid, combined with internal and surface crosslinking agents, using a polyhydric hydroxyl group-containing compound to enhance uniform crosslinking and improve absorption performance.

Benefits of technology

The composition achieves both high water absorption rate and absorption capacity under load, ensuring effective and uniform absorption characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176182000001_ABST
    Figure 2024176182000001_ABST
Patent Text Reader

Abstract

To provide a water-absorbing resin composition that balances the rate of water absorption with the absorption quantity under load, comprising a potassium salt of a water-soluble unsaturated monocarboxylic acid as a structural unit; an absorber and an absorbent article, each including the water-absorbing resin composition; and a method for producing the water-absorbing resin composition.SOLUTION: A water-absorbing resin composition contains a crosslinked polymer (A) having a structural unit derived from a potassium salt of a water-soluble unsaturated monocarboxylic acid (a1) and a structural unit derived from an internal crosslinking agent (b), with its surface crosslinked with a surface crosslinking agent (c). The water-absorbing resin composition contains a polyhydroxy group-containing compound (B) with a viscosity of 20-100 mPa s at 25°C.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a water-absorbent resin composition. [Background technology]

[0002] In sanitary materials such as paper diapers, sanitary napkins, and incontinence pads, water-absorbent resins (also called super absorbent polymers: SAPs) whose main raw materials are hydrophilic fibers such as pulp and acrylic acid (salt), etc., are widely used in the absorbent bodies. Known examples of the water-absorbent resins include sodium salt-based water-absorbent resins having a sodium salt of a water-soluble unsaturated monocarboxylic acid such as acrylic acid as a constituent unit, and potassium salt-based water-absorbent resins having a potassium salt of a water-soluble unsaturated monocarboxylic acid as a constituent unit (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 05-086251 Summary of the Invention [Problem to be solved by the invention]

[0004] In general, water absorbent resins are surface cross-linked to increase the absorption capacity under load, but the potassium salt-based water absorbent resin has a high water absorption rate, so when surface cross-linking is performed, the solution containing the surface cross-linking agent is partially absorbed before it spreads over the entire surface of the potassium salt-based water absorbent resin, and the surface cross-linking tends to be partial. Therefore, it is difficult to obtain a potassium salt-based water absorbent resin composition having a sufficient absorption capacity under load.

[0005] An object of the present invention is to provide a water-absorbent resin composition having a potassium salt of a water-soluble unsaturated monocarboxylic acid as a constituent unit, which satisfies both the water absorption rate and the absorption amount under load, an absorbent body and an absorbent article using the same, and a method for producing the water-absorbent resin composition. [Means for solving the problem]

[0006] The present invention provides a water-absorbent resin composition containing a crosslinked polymer (A) having a structure in which a surface of the crosslinked polymer (A) is crosslinked with a surface crosslinking agent (c), the crosslinked polymer (A) having a constitutional unit derived from a potassium salt of a water-soluble unsaturated monocarboxylic acid (a1) and a constitutional unit derived from an internal crosslinking agent (b), The water-absorbent resin composition contains a polyhydric hydroxyl group-containing compound (B) having a viscosity of 20 to 100 mPa·s at 25° C.; and an absorbent material and absorbent article using the same, and a water-absorbent resin composition.

[0007] The present invention provides a method for producing the water-absorbing resin composition, comprising the steps of: a polymerization step of polymerizing a monomer composition containing one or more monomers (A1) selected from the group consisting of water-soluble unsaturated monocarboxylic acids (a1) and their potassium salts, and monomers (a2) which become the water-soluble unsaturated monocarboxylic acids (a1) upon hydrolysis, and the internal crosslinking agent (b) to obtain a hydrogel containing the crosslinked polymer (A); A drying step of drying the hydrogel; and a surface crosslinking step of mixing a surface crosslinking agent composition containing the polyvalent hydroxyl group-containing compound (B) and the surface crosslinking agent (c) with the crosslinked polymer (A) and heating the mixture to surface crosslink the crosslinked polymer (A) with the surface crosslinking agent (c). Effect of the Invention

[0008] According to the present invention, it is possible to provide a water-absorbent resin composition having a potassium salt of a water-soluble unsaturated monocarboxylic acid as a constituent unit, which satisfies both the water absorption rate and the absorption amount under load, an absorbent body and an absorbent article using the same, and a method for producing the water-absorbent resin composition. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a schematic diagram showing a cross section of a cylindrical filtration tube for measuring a gel liquid permeation rate of a water-absorbent resin composition. [Diagram 2] FIG. 2 is a perspective view showing a schematic diagram of a pressure shaft and a weight for measuring a gel liquid permeation rate of a water-absorbent resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] <Water absorbent resin composition> The water absorbent resin composition of the present embodiment is a water absorbent resin composition containing a crosslinked polymer (A) having a structure in which a surface is crosslinked with a surface crosslinking agent (c), the crosslinked polymer (A) having a constitutional unit derived from a potassium salt of a water-soluble unsaturated monocarboxylic acid (a1) and a constitutional unit derived from an internal crosslinking agent (b), The water absorbent resin composition of the present embodiment contains a polyhydric hydroxyl group-containing compound (B) having a viscosity of 20 to 100 mPa s at 25° C. According to the water absorbent resin composition of the present embodiment, it is possible to provide a water absorbent resin composition having a potassium salt of a water-soluble unsaturated monocarboxylic acid as a constituent unit, which satisfies both the water absorption rate and the absorption amount under load.

[0011] [Crosslinked polymer (A)] The potassium salt of the water-soluble unsaturated monocarboxylic acid (a1) can be used without any particular limitation as long as it is a potassium salt of an unsaturated carboxylic acid having water solubility. From the viewpoint of water absorption performance when crosslinked and ease of availability, the water-soluble unsaturated carboxylic acid (a1) is preferably at least one selected from the group consisting of acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, methylene succinic acid, and citraconic acid, and more preferably at least one selected from the group consisting of acrylic acid, methacrylic acid, and methylene succinic acid.

[0012] In this specification, water-soluble means that at least 100 g of the substance dissolves in 100 g of water at 25°C.

[0013] The crosslinked polymer (A) may have a constituent unit derived from a potassium salt of the water-soluble unsaturated monocarboxylic acid (a1) and a constituent unit derived from an alkali metal salt of the water-soluble unsaturated monocarboxylic acid (a1) other than potassium. The alkali metal other than potassium is preferably sodium.

[0014] In the crosslinked polymer (A), the ratio of the number of moles of the constituent units derived from the potassium salt of the water-soluble unsaturated monocarboxylic acid (a1) to the total number of moles of the constituent units derived from the alkali metal salt of the water-soluble unsaturated monocarboxylic acid (a1) is preferably 30 mol % or more, more preferably 50 mol % or more, and further preferably 100 mol %, from the viewpoint of the absorption performance of the obtained water absorbent resin composition.

[0015] The constituent units derived from the alkali metal salt of monomer (A1) contained in the crosslinked polymer (A) can be obtained by polymerizing a monomer composition containing an alkali metal salt of monomer (A1), or by mixing a hydrous gel-like substance obtained by polymerizing a monomer composition containing the monomer (A1) but not containing an alkali metal salt with an alkali metal hydroxide to neutralize the constituent units derived from monomer (A1).

[0016] The crosslinked polymer (A) may have a structural unit derived from the alkali metal salt of the water-soluble unsaturated monocarboxylic acid (a1) together with a structural unit derived from the alkali metal salt of the water-soluble unsaturated monocarboxylic acid (a1). In the crosslinked polymer (A), the ratio of the number of moles of the structural unit derived from the alkali metal salt of the water-soluble unsaturated monocarboxylic acid (a1) to the total number of moles of the structural unit derived from the alkali metal salt of the water-soluble unsaturated monocarboxylic acid (a1) and the structural unit derived from the water-soluble unsaturated monocarboxylic acid (a1) is preferably 50 to 90 mol%, more preferably 60 to 80 mol%, from the viewpoint of suppressing irritation to the skin when it comes into contact with the skin.

[0017] The crosslinked polymer (A) may have a constituent unit derived from a potassium salt of the water-soluble unsaturated monocarboxylic acid (a1) and a constituent unit derived from another vinyl monomer (A2) copolymerizable with the water-soluble unsaturated monocarboxylic acid (a1). The vinyl monomer (A2) may be used alone or in combination of two or more kinds.

[0018] The vinyl monomer (A2) is not particularly limited, and any known hydrophobic vinyl monomer can be used (for example, the hydrophobic vinyl monomers disclosed in paragraphs 0028 to 0029 of Japanese Patent No. 3648553, and the vinyl monomers disclosed in paragraphs 0025 of Japanese Patent Laid-Open No. 2003-165883 and paragraph 0058 of Japanese Patent Laid-Open No. 2005-75982). Specifically, for example, the following vinyl monomers (i) to (iii) can be used. (i) Aromatic ethylenic monomers having 8 to 30 carbon atoms Styrene, α-methylstyrene, vinyltoluene, hydroxystyrene and other styrenes, as well as vinylnaphthalene, and halogen-substituted styrenes such as dichlorostyrene. (ii) Aliphatic ethylenic monomers having 2 to 20 carbon atoms Alkenes (such as ethylene, propylene, butene, isobutylene, pentene, heptene, diisobutylene, octene, dodecene, and octadecene); and alkadienes (such as butadiene and isoprene). (iii) Alicyclic ethylenic monomers having 5 to 15 carbon atoms Monoethylenically unsaturated monomers (such as pinene, limonene, and indene); and polyethylenic vinyl monomers (such as cyclopentadiene, bicyclopentadiene, and ethylidene norbornene).

[0019] In the crosslinked polymer (A), the ratio of the number of moles of the constituent units derived from the vinyl monomer (A2) to the total number of moles of the constituent units derived from the alkali metal salt of the water-soluble unsaturated monocarboxylic acid (a1), the constituent units derived from the water-soluble unsaturated monocarboxylic acid (a1), and the constituent units derived from the vinyl monomer (A2) is preferably 0 to 5 mol%, more preferably 0 to 3 mol%, even more preferably 0 to 1.5 mol%, and even more preferably 0 mol%, from the viewpoint of absorption performance, etc.

[0020] [Internal crosslinking agent (b)] The internal crosslinking agent (b) is not particularly limited, and known crosslinking agents can be used (for example, a crosslinking agent having two or more ethylenically unsaturated groups disclosed in paragraphs 0031 to 0034 of Japanese Patent No. 3648553, a crosslinking agent having at least one functional group capable of reacting with a water-soluble substituent and at least one ethylenically unsaturated group, and a crosslinking agent having at least two functional groups capable of reacting with a water-soluble substituent, a crosslinking agent having two or more ethylenically unsaturated groups disclosed in paragraphs 0028 to 0031 of Japanese Patent Publication No. 2003-165883, a crosslinking agent having an ethylenically unsaturated group and a reactive functional group, and a crosslinking agent having two or more reactive substituents, a crosslinkable vinyl monomer disclosed in paragraph 0059 of Japanese Patent Publication No. 2005-75982, and a crosslinkable vinyl monomer disclosed in paragraphs 0015 to 0016 of Japanese Patent Publication No. 2005-95759).

[0021] The internal crosslinking agent (b) is preferably a crosslinking agent having two or more ethylenically unsaturated groups, and from the viewpoint of reactivity with monomers and water absorption properties, a polyhydric (meth)allyl compound and an acrylamide compound having two or more ethylenically unsaturated groups are preferred, and one or more selected from the group consisting of polyhydric alcohols such as alkylene glycol, trimethylolpropane, glycerin, pentaerythritol and sorbitol, polyhydric (meth)allyl compounds such as tetraallyloxyethane and triallyl isocyanurate, and compounds represented by the following general formula (1) are more preferred. The internal crosslinking agent (b) may be used alone or in combination of two or more.

[0022] [ka] [In general formula (1), R 1 and R 2 Each of X is independently a hydrogen atom or a methyl group. 1 is an n-valent organic group having an aliphatic group having one or more carbon atoms and optionally containing a nitrogen atom, an oxygen atom, or a sulfur atom, and the aliphatic group may be linear or branched. n is an integer of 2 to 6.

[0023] Examples of commercially available products of the compound represented by the general formula (1) include methylenebisacrylamide and FOM-03006, FOM-03007, FOM-03008, and FOM-03009 manufactured by Fuji Film Corporation.

[0024] In the crosslinked polymer (A), the ratio of the number of moles of the structural units derived from the internal crosslinking agent (b) to the total number of moles of the structural units derived from the alkali metal salt of the water-soluble unsaturated monocarboxylic acid (a1), the structural units derived from the water-soluble unsaturated monocarboxylic acid (a1), and the structural units derived from the vinyl monomer (A2) is preferably 0.001 to 5, more preferably 0.005 to 3, and even more preferably 0.005 to 1, from the viewpoint of absorption performance, etc.

[0025] [Surface cross-linking agent (c)] The water-absorbent resin composition has a structure in which the surface of the crosslinked polymer (A) is crosslinked by a surface crosslinking agent (c). By crosslinking the surface of the crosslinked polymer (A), the gel strength of the water-absorbent resin composition can be improved, and the desired water retention and absorption amount under load can be satisfied. The surface crosslinking agent (c) can be either inorganic or organic. As the surface crosslinking agent (c), known organic surface crosslinking agents can be used (such as polyvalent glycidyl compounds, polyvalent amines, polyvalent aziridine compounds, and polyvalent isocyanate compounds described in JP-A-59-189103, polyhydric alcohols described in JP-A-58-180233 and JP-A-61-16903, silane coupling agents described in JP-A-61-211305 and JP-A-61-252212, alkylene carbonates described in JP-T-5-508425, and polyvalent oxazoline compounds described in JP-A-11-240959). Among these surface cross-linking agents (c), from the viewpoint of economic efficiency and absorption characteristics, polyhydric glycidyl compounds, polyhydric alcohols and polyhydric amines are preferred, more preferred are polyhydric glycidyl compounds and polyhydric alcohols, particularly preferred are polyhydric glycidyl compounds, and most preferred is ethylene glycol diglycidyl ether. The surface cross-linking agents (c) may be used alone or in combination of two or more.

[0026] The amount (wt%) of the surface cross-linking agent (c) used is not particularly limited since it can be variously changed depending on the type, cross-linking conditions, targeted performance, and the like, but is preferably 0.001 to 3, more preferably 0.005 to 2, and further preferably 0.01 to 1.5 based on the weight of the water absorbent resin composition from the viewpoint of the water retention capacity of the water absorbent resin composition.

[0027] [Polyhydroxyl group-containing compound (B)] The water absorbent resin composition contains a polyhydric hydroxyl group-containing compound (B) having a viscosity of 20 to 100 mPa·s at 25° C. The inclusion of the polyhydric hydroxyl group-containing compound (B) in the water absorbent resin composition has the advantage of contributing to the prevention of breakage of the water absorbent resin composition and stability against changes over time, and the viscosity of the polyhydric hydroxyl group-containing compound (B) at 25° C. being 20 to 100 mPa·s improves the gel strength of the water absorbent resin composition, making it possible to provide a water absorbent resin composition excellent in water retention capacity and absorption capacity under load.

[0028] Examples of the polyhydric hydroxyl group-containing compound (B) include ethylene glycol (viscosity at 25° C.: 21 mPa·s), diethylene glycol (viscosity at 25° C.: 36 mPa·s), triethylene glycol (viscosity at 25° C.: 48 mPa·s), propylene glycol (viscosity at 25° C.: 48 mPa·s), 1,2-butanediol (viscosity at 25° C.: 40 mPa·s), 1,3-butanediol (viscosity at 25° C.: 45 mPa·s), 1,4-butanediol (viscosity at 25° C.: 65 mPa·s), 1,2-pentanediol (viscosity at 25° C.: 60 mPa·s), etc. Among these polyhydric hydroxyl group-containing compounds (B), from the viewpoints of gel strength, water retention, and absorption properties under load of the water absorbent resin composition, polyhydric alcohols are preferred, and one or more selected from the group consisting of diethylene glycol, propylene glycol, and 1,4-butanediol are more preferred. The polyhydric hydroxyl group-containing compound (B) may be used alone or in combination of two or more kinds. In this specification, the viscosity of the polyhydric hydroxyl group-containing compound (B) at 25°C is measured by the method described in the Examples.

[0029] The content (wt%) of the polyvalent hydroxyl group-containing compound (B) in the solid content of the water absorbent resin composition is not particularly limited because it can be changed depending on crosslinking conditions, target performance, etc., but is preferably 0.1 to 5, more preferably 0.2 to 3.0, and even more preferably 0.3 to 1.5 from the viewpoint of the absorption performance of the water absorbent resin composition. The content (wt%) of the polyvalent hydroxyl group-containing compound (B) in the solid content of the water absorbent resin composition can be measured by the following method.

[0030] 5.0 g of the solid content of the water absorbent resin composition is thoroughly cooled with liquid nitrogen and pulverized with a freezing pulverizer. 2.000 g of the pulverized solid content of the water absorbent resin composition is placed in a 50 ml screw tube, and 20 ml of 80% aqueous methanol solution and a stirrer are added, and the tube is closed and stirred at 400 rpm for 1.5 hours, and then allowed to stand for 10 minutes. Next, 5 ml of the supernatant liquid from the screw tube is collected and filtered with a membrane filter (GL Science GL Chromatodisc, pore size: 0.2 μm), and the filtrate is measured by gas chromatography under the following conditions. The measured value is compared with the calibration curve to calculate the content of the polyvalent hydroxyl group-containing compound (B) in the solid content of the water absorbent resin composition. [Measurement conditions] (1) Equipment: Gas chromatograph Nexis GC-2030, manufactured by Shimadzu Corporation (2) Column: ZB-WAX 30m x 0.25mmφ x 0.25μm (3) Eluent: methanol / water = 80 / 20 (volume ratio) (4) Injection conditions: carrier gas: nitrogen, column flow rate: 1.47 ml / min, column temperature: 80° C. (5) Calibration curve: 0.600 g of the organic solvent to be measured is placed in a 20 ml measuring flask, and then diluted with 60% aqueous methanol to prepare a sample of a 3.0% solution by weight. Next, using the 3.0% solution, samples for the calibration curve of concentrations of 0.3%, 0.2%, and 0.1% are prepared.

[0031] [Other ingredients] The water-absorbent resin composition may contain other components to a certain extent without impairing its performance. Examples of the other components include the following hydrophobic substance (C), antibacterial agent (such as a cationic surfactant), preservative, antifungal agent, ultraviolet absorber, antioxidant, colorant, fragrance, deodorant, liquid permeability improver, powder flow improver, and organic fibrous material. The amount of the other components is usually 5% by weight or less based on the weight of the water-absorbent resin composition.

[0032] [Hydrophobic Substance (C)] The water-absorbing resin composition may contain a hydrophobic substance (C). The hydrophobic substance (C) includes a hydrophobic substance (C1) containing a hydrocarbon group, a hydrophobic substance (C2) containing a hydrocarbon group having a fluorine atom, and a hydrophobic substance (C3) having a polysiloxane structure.

[0033] Examples of the hydrophobic substance (C1) containing a hydrocarbon group include polyolefin resins, polyolefin resin derivatives, polystyrene resins, polystyrene resin derivatives, waxes, long-chain fatty acid esters, long-chain fatty acids and their salts, long-chain aliphatic alcohols, alkylene oxide adducts of long-chain aliphatic alcohols, long-chain aliphatic amides, and mixtures of two or more of these.

[0034] Examples of polyolefin resins include polymers having a weight average molecular weight of 1,000 to 1,000,000, which contain an olefin having 2 to 4 carbon atoms {ethylene, propylene, isobutylene, isoprene, etc.} as an essential constituent monomer (the olefin content is at least 50% by weight based on the weight of the polyolefin resin) {for example, polyethylene, polypropylene, polyisobutylene, poly(ethylene-isobutylene), isoprene, etc.}.

[0035] Examples of polyolefin resin derivatives include polymers having a weight average molecular weight of 1,000 to 1,000,000, in which a carboxy group (-COOH) or 1,3-oxo-2-oxapropylene (-COOCO-) has been introduced into a polyolefin resin {for example, thermal degradation products of polyethylene, thermal degradation products of polypropylene, maleic acid modified polyethylene, chlorinated polyethylene, maleic acid modified polypropylene, ethylene-acrylic acid copolymer, ethylene-maleic anhydride copolymer, isobutylene-maleic anhydride copolymer, maleated polybutadiene, ethylene-vinyl acetate copolymer, and maleated products of ethylene-vinyl acetate copolymer}.

[0036] As the polystyrene resin, a polymer having a weight average molecular weight of 1,000 to 1,000,000 can be used.

[0037] Examples of polystyrene resin derivatives include polymers having a weight average molecular weight of 1,000 to 1,000,000, which contain styrene as an essential constituent monomer (the styrene content is at least 50% by weight, based on the weight of the polystyrene derivative) {for example, styrene-maleic anhydride copolymer, styrene-butadiene copolymer, and styrene-isobutylene copolymer, etc.}.

[0038] Examples of the wax include waxes having a melting point of 50 to 200° C. {for example, paraffin wax, beeswax, carnauba wax, beef tallow, etc.}.

[0039] Examples of the long-chain fatty acid ester include esters of fatty acids having 8 to 30 carbon atoms and alcohols having 1 to 12 carbon atoms {for example, methyl laurate, ethyl laurate, methyl stearate, ethyl stearate, methyl oleate, ethyl oleate, glycerol monolaurate, glycerol monostearate, glycerol monooleate, pentaerythritol monolaurate, pentaerythritol monostearate, pentaerythritol monooleate, sorbitan fatty acid esters (sorbitol monolaurate, sorbitol monostearate, and sorbitol monooleate, etc.), sucrose fatty acid esters (sucrose palmitate monoester, sucrose palmitate diester, sucrose palmitate triester, sucrose monostearate, sucrose distearate, and sucrose stearate triester, etc.), and beef tallow}.

[0040] Examples of long-chain fatty acids and salts thereof include fatty acids having 8 to 30 carbon atoms {for example, lauric acid, palmitic acid, stearic acid, oleic acid, dimer acid, and behenic acid}, and examples of their salts include salts with zinc, calcium, magnesium, or aluminum (hereinafter abbreviated as Zn, Ca, Mg, and Al, respectively) {for example, Ca palmitate, Al palmitate, Ca stearate, Mg stearate, and Al stearate}.

[0041] Examples of long-chain aliphatic alcohols include aliphatic alcohols having 8 to 30 carbon atoms {for example, lauryl alcohol, palmityl alcohol, stearyl alcohol, oleyl alcohol, etc.}. From the viewpoint of leakage resistance of the absorbent article, palmityl alcohol, stearyl alcohol, oleyl alcohol, and pentadecyl alcohol are preferred, and stearyl alcohol is more preferred.

[0042] Examples of the alkylene oxide adduct of a long-chain aliphatic alcohol include the above-mentioned alkylene oxide (preferably an alkylene oxide having 2 to 4 carbon atoms) adduct (number of moles added = 1 to 5) of a long-chain aliphatic alcohol. From the viewpoint of leakage resistance of an absorbent article, an ethylene oxide 2-mol adduct of oleyl alcohol and an ethylene oxide 4-mol adduct of pentadecyl alcohol are preferred, and an ethylene oxide 4-mol adduct of pentadecyl alcohol is more preferred.

[0043] Examples of the long-chain aliphatic amide include an amidation product of a long-chain aliphatic primary amine having 8 to 30 carbon atoms with a carboxylic acid having a hydrocarbon group having 1 to 30 carbon atoms, an amidation product of ammonia or a primary amine having 1 to 7 carbon atoms with a long-chain fatty acid having 8 to 30 carbon atoms, an amidation product of a long-chain aliphatic secondary amine having at least one aliphatic chain having 8 to 30 carbon atoms with a carboxylic acid having 1 to 30 carbon atoms, and an amidation product of a secondary amine having two aliphatic hydrocarbon groups having 1 to 7 carbon atoms with a long-chain fatty acid having 8 to 30 carbon atoms.

[0044] The amidation product of a long-chain aliphatic primary amine having 8 to 30 carbon atoms and a carboxylic acid having a hydrocarbon group having 1 to 30 carbon atoms can be divided into a product in which a primary amine reacts with a carboxylic acid in a 1:1 ratio and a product in which a primary amine reacts with a carboxylic acid in a 1:2 ratio. Examples of the product in which a primary amine reacts with a carboxylic acid in a 1:1 ratio include acetic acid N-octylamide, acetic acid N-hexacosylamide, heptacosanoic acid N-octylamide, and heptacosanoic acid N-hexacosylamide. Examples of the product in which a primary amine reacts with a carboxylic acid in a 1:2 ratio include diacetic acid N-octylamide, diacetic acid N-hexacosylamide, diheptacosanoic acid N-octylamide, and diheptacosanoic acid N-hexacosylamide. In the case of a product in which a primary amine reacts with a carboxylic acid in a 1:2 ratio, the carboxylic acids used may be the same or different.

[0045] Amidation products of ammonia or a primary amine having 1 to 7 carbon atoms and a long-chain fatty acid having 8 to 30 carbon atoms are divided into products in which ammonia or a primary amine reacts with a carboxylic acid in a 1:1 ratio and products in which ammonia or a primary amine reacts with a carboxylic acid in a 1:2 ratio. Examples of the products in a 1:1 ratio include nonanoic acid amide, nonanoic acid methylamide, nonanoic acid N-heptylamide, heptacosanoic acid amide, heptacosanoic acid N-methylamide, heptacosanoic acid N-heptylamide, and heptacosanoic acid N-hexacosylamide. Examples of the product obtained by the reaction in a ratio of 1:2 include dinonanoic acid amide, dinonanoic acid N-methylamide, dinonanoic acid N-heptylamide, dioctadecanoic acid amide, dioctadecanoic acid N-ethylamide, dioctadecanoic acid N-heptylamide, diheptacosanoic acid amide, diheptacosanoic acid N-methylamide, diheptacosanoic acid N-heptylamide, diheptacosanoic acid N-hexacosylamide, etc. In addition, in the product obtained by the reaction of ammonia or a primary amine with a carboxylic acid in a ratio of 1:2, the carboxylic acids used may be the same or different.

[0046] Examples of the amidation products of long-chain aliphatic secondary amines having at least one aliphatic chain having 8 to 30 carbon atoms with carboxylic acids having 1 to 30 carbon atoms include acetic acid N-methyloctylamide, acetic acid N-methylhexacosylamide, acetic acid N-octylhexacosylamide, acetic acid N-dihexacosylamide, heptacosanoic acid N-methyloctylamide, heptacosanoic acid N-methylhexacosylamide, heptacosanoic acid N-octylhexacosylamide, and heptacosanoic acid N-dihexacosylamide.

[0047] Examples of the amidation products of secondary amines having two aliphatic hydrocarbon groups having 1 to 7 carbon atoms with long-chain fatty acids having 8 to 30 carbon atoms include nonanoic acid N-dimethylamide, nonanoic acid N-methylheptylamide, nonanoic acid N-diheptylamide, heptacosanoic acid N-dimethylamide, heptacosanoic acid N-methylheptylamide, and heptacosanoic acid N-diheptylamide.

[0048] The hydrophobic substance (C2) containing a hydrocarbon group having a fluorine atom includes perfluoroalkanes, perfluoroalkenes, perfluoroaryls, perfluoroalkyl ethers, perfluoroalkyl carboxylic acids, perfluoroalkyl alcohols, and mixtures of two or more of these.

[0049] Examples of the hydrophobic substance (C3) having a polysiloxane structure include polydimethylsiloxane, polyether-modified polysiloxane (polyoxyethylene-modified polysiloxane, poly(oxyethylene-oxypropylene)-modified polysiloxane, etc.), carboxy-modified polysiloxane, epoxy-modified polysiloxane, amino-modified polysiloxane, alkoxy-modified polysiloxane, and mixtures thereof.

[0050] The hydrophobic substance (C) has an HLB value according to the Griffin method of preferably 1 to 10, more preferably 2 to 8, and particularly preferably 3 to 7. Within this range, blocking resistance during initial swelling is further improved. The HLB value according to the Griffin method is a value indicating the balance between the hydrophobicity and hydrophilicity of a surfactant, and takes a value from 1 to 20, with a smaller value indicating stronger hydrophobicity and a larger value indicating stronger hydrophilicity. The HLB value according to the Griffin method is a value calculated from the following formula 1, and in the following formula 1, "sum of formula weights of hydrophilic groups / molecular weight" means the weight % of hydrophilic groups. Formula 1) Griffin method: HLB value = 20 x (sum of formula weights of hydrophilic groups / molecular weight)

[0051] Among the hydrophobic substances (C), from the viewpoint of blocking resistance during initial swelling, hydrophobic substances (C1) containing a hydrocarbon group are preferred, more preferably long-chain fatty acid esters and alkylene oxide adducts of long-chain fatty alcohols, and even more preferably sucrose fatty acid esters, 2-mol ethylene oxide adducts of oleyl alcohol (HLB=4), and 4-mol ethylene oxide adducts of pentadecyl alcohol (HLB=9).

[0052] Among sucrose fatty acid esters, sucrose fatty acid esters having an HLB value of 10 or less are preferred, and sucrose stearates containing 50% or more di- or tri-polyesters [trade names: Ryoto Sugar Ester S-970 (HLB=9), Ryoto Sugar Ester S-370 (HLB=3), Ryoto Sugar Ester S-070 (HLB=1 or less), etc.] are particularly preferred.

[0053] The amount (wt %) of the hydrophobic substance (C) used is preferably 0.001 to 1, more preferably 0.005 to 0.5, and even more preferably 0.01 to 0.3, based on the weight of the crosslinked polymer (A) from the viewpoints of absorption performance and blocking resistance during initial swelling.

[0054] The water-retaining capacity (g / g) of the water-absorbent resin composition in 0.9 wt % physiological saline (hereinafter also referred to as water-retaining capacity) is preferably 39 or more and less than 55, more preferably 40 or more and less than 50, and even more preferably 41 or more and less than 46. If it is within this range, when it is used as an absorbent, liquid leakage is unlikely to occur. The water-retaining capacity can be appropriately adjusted by the type and amount of the internal cross-linking agent (b) and the surface cross-linking agent (c). The water-retaining capacity can be measured by the method described in the Examples.

[0055] The water absorbent resin composition has an absorption speed by a vortex method of preferably 30 seconds or less, more preferably 28 seconds or less, and particularly preferably 25 seconds or less, from the viewpoints of suppressing leakage and maintaining surface dryness of an absorbent article. The water absorption speed by the vortex method can be measured by the method described in the Examples.

[0056] From the viewpoint of the absorption rate of the diaper, the gel liquid permeation rate (ml / min) of the water-absorbent resin composition is preferably 5 to 300, more preferably 10 to 280, and further preferably 15 to 250. The gel liquid permeation rate of the water-absorbent resin composition can be measured by the method described in the Examples.

[0057] The water-absorbent resin composition preferably has an absorption capacity under load of 10 g / g or more, more preferably 13 or more. When the absorption capacity is within this range, the diaper is excellent in absorption and liquid return under load. The absorption capacity under load of the water-absorbent resin composition can be measured by the method described in the Examples.

[0058] The shape of the water absorbent resin composition is not particularly limited, and examples thereof include particles in the form of irregularly crushed particles, scales, pearls, rice grains, etc. Among these, irregularly crushed particles are preferred from the viewpoint of good entanglement with fibrous materials in applications such as paper diapers, and no risk of falling off from the fibrous materials.

[0059] The apparent density (g / ml) of the water absorbent resin composition is preferably 0.54 to 0.70, more preferably 0.56 to 0.68, and even more preferably 0.58 to 0.66. When it is in the range of 0.54 to 0.70, the absorption performance becomes even better. The apparent density is measured at 25°C in accordance with JIS K7365:1999.

[0060] <Method of producing water-absorbent resin composition> The manufacturing method of the present embodiment is a manufacturing method of the water absorbent resin composition, a polymerization step of polymerizing a monomer composition containing one or more monomers (A1) selected from the group consisting of the water-soluble unsaturated monocarboxylic acid (a1) and its potassium salt, and a monomer (a2) which becomes the water-soluble unsaturated monocarboxylic acid (a1) upon hydrolysis, and the internal crosslinking agent (b) to obtain a hydrogel containing the crosslinked polymer (A); A drying step of drying the hydrogel; and a surface crosslinking step of mixing a surface crosslinking agent composition containing the polyvalent hydroxyl group-containing compound (B) and the surface crosslinking agent (c) with the crosslinked polymer (A) and heating the mixture to surface crosslink the crosslinked polymer (A) with the surface crosslinking agent (c).

[0061] [Polymerization process] The production method of this embodiment includes a polymerization step of polymerizing a monomer composition containing one or more monomers (A1) selected from the group consisting of the water-soluble unsaturated monocarboxylic acid (a1) and its potassium salt, and a monomer (a2) that becomes the water-soluble unsaturated monocarboxylic acid (a1) upon hydrolysis, and the internal crosslinking agent (b) to obtain a hydrogel containing the crosslinked polymer (A).

[0062] [Monomer (a2)] A monomer (a2) which becomes the water-soluble unsaturated carboxylic acid (a1) by hydrolysis can be used together with or instead of the water-soluble unsaturated carboxylic acid (a1). The monomer (a2) is not particularly limited, and examples thereof include a monomer having one hydrolyzable substituent which becomes a carboxyl group by hydrolysis. Examples of the hydrolyzable substituent include a group containing an acid anhydride (1,3-oxo-1-oxapropylene group, -COO-CO-), a group containing an ester bond (alkyloxycarbonyl, vinyloxycarbonyl, allyloxycarbonyl or propenyloxycarbonyl, -COOR), and a cyano group. Here, R is an alkyl group having 1 to 3 carbon atoms (methyl, ethyl, and propyl), vinyl, allyl, and propenyl.

[0063] In this specification, the term "hydrolyzable" in the monomer (a2) means a property of being hydrolyzed by the action of water and, if necessary, a catalyst (such as an acid or a base) to become water-soluble. The hydrolysis of the monomer (a2) may be carried out during or after polymerization, or both, but is preferably carried out after polymerization from the viewpoint of the absorption performance of the resulting water absorbent resin composition.

[0064] As the polymerization method of the monomer composition, the preferred method includes solution polymerization using a polymerization solvent and reversed-phase suspension polymerization.Among the polymerization methods of the monomer composition, the preferred method is the solution polymerization method, and the particularly preferred method is the aqueous solution polymerization method using water as a polymerization solvent, since it does not need to use an organic solvent and is advantageous in terms of production cost, and the most preferred method is the aqueous solution polymerization method, which uses water as a polymerization solvent, since it can obtain a water-absorbing resin composition with a large water retention capacity and a small amount of water-soluble components, and does not need to control the temperature during polymerization.

[0065] When the reverse phase suspension polymerization method is used as the polymerization method, the polymerization can be carried out using a hydrocarbon solvent such as xylene, normal hexane, or normal heptane, and, if necessary, the polymerization may be carried out in the presence of a conventionally known dispersant or surfactant.

[0066] When the monomer composition is polymerized by aqueous solution polymerization, a mixed solvent containing water and an organic solvent can be used as the polymerization solvent, and examples of the organic solvent include methanol, ethanol, acetone, methyl ethyl ketone, N,N-dimethylformamide, dimethyl sulfoxide, and a mixture of two or more of these. When the monomer composition is polymerized by aqueous solution polymerization, the amount (wt%) of the organic solvent used is preferably 40 or less, more preferably 30 or less, based on the weight of water.

[0067] In the case of performing the aqueous solution polymerization, the concentration of the monomer composition containing the monomer (A1) and the internal crosslinking agent (b) contained in the polymerization solution, and in the case of using the vinyl monomer (A2), the concentration of the monomer composition containing the monomer (A1), the vinyl monomer (A2), and the internal crosslinking agent (b) is preferably 10 to 50% by weight, more preferably 15 to 40% by weight, based on the total weight of the polymerization solution.

[0068] When a catalyst is used for polymerization, a conventionally known radical polymerization catalyst can be used, for example, azo compounds [azobisisobutyronitrile, azobiscyanovaleric acid, 2,2'-azobis(2-amidinopropane)hydrochloride, etc.], inorganic peroxides (hydrogen peroxide, ammonium persulfate, potassium persulfate, sodium persulfate, etc.), organic peroxides [benzoyl peroxide, di-t-butyl peroxide, cumene hydroperoxide, succinic acid peroxide, di(2-ethoxyethyl)peroxydicarbonate, etc.], and redox catalysts (combinations of reducing agents such as alkali metal sulfite or bisulfite, ammonium sulfite, ammonium bisulfite, and ascorbic acid with oxidizing agents such as alkali metal persulfate, ammonium persulfate, hydrogen peroxide, and organic peroxides), etc. These catalysts may be used alone or in combination of two or more of them.

[0069] The amount (wt %) of the radical polymerization catalyst used is preferably 0.0005 to 5, and more preferably 0.001 to 2, based on the total weight of the monomer (A1) and the alkali metal salt of the monomer (A1), and when the vinyl monomer (A2) is used, based on the total weight of the monomer (A1), the alkali metal salt of the monomer (A1), and the vinyl monomer (A2).

[0070] During polymerization, a polymerization control agent such as a chain transfer agent may be used in combination as necessary, and specific examples of such agents include sodium hypophosphite, sodium phosphite, alkyl mercaptans, alkyl halides, thiocarbonyl compounds, etc. These polymerization control agents may be used alone, or two or more of them may be used in combination.

[0071] The amount (wt %) of the polymerization control agent used is preferably 0.0005 to 5, and more preferably 0.001 to 2, based on the total weight of the monomer (A1) and the alkali metal salt of the monomer (A1), and when the vinyl monomer (A2) is used, based on the total weight of the monomer (A1), the alkali metal salt of the monomer (A1), and the vinyl monomer (A2).

[0072] The polymerization initiation temperature can be appropriately adjusted depending on the type of catalyst used, but is preferably 0 to 100° C., more preferably 2 to 80° C. The temperature reached during polymerization is preferably 50° C. or higher, more preferably 60° C. or higher, from the viewpoint of reactivity.

[0073] When a solvent (organic solvent, water, etc.) is used in the polymerization, it is preferable to distill off the solvent after the polymerization. When the solvent contains an organic solvent, the content (wt%) of the organic solvent after distillation is preferably 0 to 10, more preferably 0 to 5, further preferably 0 to 3, and even more preferably 0 to 1, based on the weight of the crosslinked polymer (A). When it is within this range, the absorption performance of the water absorbent resin composition becomes further improved.

[0074] When the solvent contains water, the water content (wt %) after distillation based on the weight of the crosslinked polymer (A) is preferably 0 to 20, more preferably 1 to 10, further preferably 2 to 9, and even more preferably 3 to 8. When it is within this range, the absorption performance becomes further improved.

[0075] The solvent content or moisture content is determined from the weight loss of a measurement sample when heated using an infrared moisture meter [such as JE400 manufactured by KETT Co., Ltd.: 120±5°C, 30 minutes, atmospheric humidity before heating 50±10% RH, lamp specifications 100V, 40W].

[0076] By the above-mentioned polymerization method, a water-containing gel-like material (hereinafter, also referred to as water-containing gel) in which the crosslinked polymer (A) contains water can be obtained.

[0077] [Chopping process] The method for producing the water-absorbing resin composition of the present embodiment may include a shredding step of shredding the hydrogel, if necessary. The size (longest diameter) of the gel after shredding is preferably 50 μm to 10 cm, more preferably 100 μm to 2 cm, and even more preferably 1 mm to 1 cm. When the size is within this range, the drying property in the drying step is further improved.

[0078] The chopping can be carried out by a known method, and can be carried out using a chopping device (for example, a Becks mill, a rubber chopper, a Farma mill, a mincing machine, an impact grinder, and a roll grinder).

[0079] In the production of the water-absorbing resin composition, when the hydrous gel-like material is neutralized, a method of neutralizing the hydrous gel-like material by mixing the base with the hydrous gel-like material in the cutting step is preferred.

[0080] As the base, alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, and alkali metal carbonates such as sodium carbonate, sodium hydrogen carbonate and potassium carbonate can usually be used.

[0081] [Drying process] The method for producing a water-absorbent resin composition of the present embodiment includes a drying step of drying the water-containing gel and distilling off the solvent (including water) in the water-containing gel to obtain a water-absorbent resin composition.

[0082] In the drying step, examples of a method for distilling off the solvent in the hydrogel include distillation (drying) with hot air at a temperature of 80 to 230°C, thin-film drying using a drum dryer heated to 100 to 230°C, (heated) reduced pressure drying, freeze drying, drying by infrared rays, decantation, filtration, and the like.

[0083] [Crushing process] The method for producing the water absorbent resin composition of the present embodiment may include a pulverization step of pulverizing the water absorbent resin composition obtained in the drying step to obtain a particulate water absorbent resin composition containing the crosslinked polymer (A).

[0084] In the pulverization step, the method for pulverizing the water absorbent resin composition containing the crosslinked polymer (A) is not particularly limited, and a pulverizing device (e.g., a hammer type pulverizer, an impact type pulverizer, a roll type pulverizer, and a Schett airflow type pulverizer) can be used. The pulverized water absorbent resin composition can be adjusted in particle size by sieving, etc., if necessary.

[0085] [Surface crosslinking process] The method for producing a water absorbent resin composition of the present embodiment includes a surface crosslinking step of mixing a surface crosslinking agent composition containing the polyvalent hydroxyl group-containing compound (B) and the surface crosslinking agent (c) with the crosslinked polymer (A), and heating the mixture to surface crosslink the crosslinked polymer (A) with the surface crosslinking agent (c).

[0086] The water absorbent resin composition obtained through the surface cross-linking step has a structure in which the surface of the cross-linked polymer (A) is cross-linked by the surface cross-linking agent (c). By cross-linking the surface of the cross-linked polymer (A), the gel strength of the water absorbent resin composition can be improved, and the desired water retention capacity and absorption capacity under load of the water absorbent resin composition can be satisfied. In addition, when the cross-linked polymer (A) is surface-cross-linked with the surface cross-linking agent (c), the surface cross-linking agent (c) is diluted with the polyvalent hydroxyl group-containing compound (B) and used to improve the uniformity of the surface cross-linking, and the desired water retention capacity of the water absorbent resin composition and the reduction in the amount of fine powder generated due to the improvement in gel strength can be satisfied.

[0087] The reason why the uniformity of the surface crosslinking of the crosslinked polymer (A) is improved by diluting the surface crosslinking agent (c) with the polyvalent hydroxyl group-containing compound (B) is not clear, but it can be presumed that the use of the polyvalent hydroxyl group-containing compound (B) as a solvent controls the rate at which the crosslinked polymer (A) absorbs the surface crosslinking agent composition, and as a result, uniform surface crosslinking can be realized.

[0088] The content of the polyvalent hydroxyl group-containing compound (B) in the surface crosslinking agent composition is preferably 10% by weight or more, more preferably 15% by weight or more, and still more preferably 20% by weight or more, from the viewpoint of controlling the rate at which the crosslinked polymer (A) absorbs the surface crosslinking agent, and is preferably 60% by weight or less, more preferably 55% by weight or less, and still more preferably 50% by weight or less, from the viewpoint of the reactivity of the surface crosslinking agent (c) and the handleability of the crosslinked polymer (A) after the addition of the surface crosslinking agent composition.

[0089] The content of the surface crosslinking agent (c) in the surface crosslinking agent composition is preferably 0.4% by weight or more, more preferably 0.8% by weight or more, and still more preferably 1.2% by weight or more, from the viewpoint of handleability of the crosslinked polymer after addition of the crosslinking agent composition, and is preferably 5.0% by weight or less, more preferably 4.5% by weight or less, and still more preferably 3.5% by weight or less, from the viewpoint of uniformly adding the crosslinking agent composition.

[0090] The surface crosslinking of the crosslinked polymer (A) can be carried out by mixing the crosslinked polymer (A) with the surface crosslinking agent composition and heating. The crosslinked polymer (A) can be mixed with the surface crosslinking agent (c) and the polyvalent hydroxyl group-containing compound (B) in a mixing apparatus such as a cylindrical mixer, a screw mixer, a screw extruder, a turbulizer, a Nauter mixer, a double-arm kneader, a flow mixer, a V-type mixer, a mince mixer, a ribbon mixer, a flow mixer, an airflow mixer, a rotating disk mixer, a conical blender, and a roll mixer to uniformly mix the crosslinked polymer (A) with the surface crosslinking agent (c) and the polyvalent hydroxyl group-containing compound (B).

[0091] After mixing the crosslinked polymer (A) and the surface crosslinking agent composition, a heat treatment is performed. The heating temperature is preferably 100 to 180°C, more preferably 110 to 170°C, and even more preferably 120 to 160°C from the viewpoint of the breakage resistance of the water absorbent resin composition. If the heating temperature is 180°C or less, indirect heating using steam is possible, which is advantageous in terms of equipment, and if the heating temperature is less than 100°C, the absorption performance may deteriorate. In addition, the heating time can be appropriately set depending on the heating temperature, but from the viewpoint of the absorption performance, it is preferably 5 to 60 minutes, more preferably 10 to 40 minutes.

[0092] After the surface of the crosslinked polymer (A) is crosslinked with the surface crosslinking agent (c), the particle size is adjusted by sieving if necessary. The average particle size of the obtained particles is preferably 100 to 600 μm, more preferably 200 to 500 μm. The content of fine particles is preferably low, and the content of particles of 100 μm or less is preferably 3 wt % or less, and the content of particles of 150 μm or less is more preferably 3 wt % or less.

[0093] <Absorbent> The water-absorbent resin composition can be used to obtain an absorbent. The water-absorbent resin composition may be used alone or together with other materials to produce an absorbent. Examples of such other materials include fibrous materials. The structure and manufacturing method of the absorbent when used together with fibrous materials are known (JP Patent Publication No. 2003-225565, JP Patent Publication No. 2006-131, etc.). This is similar to Japanese Patent Application Publication No. 767 and Japanese Patent Application Publication No. 2005-097569, etc.

[0094] The preferred fibrous materials are cellulosic fibers, organic synthetic fibers, and mixtures of cellulosic fibers and organic synthetic fibers.

[0095] Examples of cellulosic fibers include natural fibers such as fluff pulp, and cellulosic chemical fibers such as viscose rayon, acetate, and cupra. The raw materials (coniferous and broad-leaved trees, etc.) and manufacturing methods (chemical pulp, semi-chemical pulp, etc.) of these cellulosic natural fibers are The type of pulp used (e.g., mechanical pulp, CTMP, etc.) and the bleaching method are not particularly limited.

[0096] Examples of organic synthetic fibers include polypropylene fibers, polyethylene fibers, polyamide fibers, polyacrylonitrile fibers, polyester fibers, polyvinyl alcohol fibers, polyurethane fibers, and heat-fusible composite fibers (fibers in which at least two of the above-mentioned fibers having different melting points are composited in a sheath-core type, eccentric type, parallel type, or other type, fibers in which at least two of the above-mentioned fibers are blended, and fibers in which the surface layer of the above-mentioned fibers has been modified, etc.).

[0097] Among these fibrous materials, preferred are cellulose-based natural fibers, polypropylene-based fibers, polyethylene-based fibers, polyester-based fibers, heat-fusible composite fibers, and mixed fibers thereof. More preferred are fluff pulp, heat-fusible composite fibers, and mixed fibers thereof, in that the obtained water absorbent has excellent shape retention after absorbing water.

[0098] The length and thickness of the fibrous material are not particularly limited, and any length within the range of 1 to 200 mm and any thickness within the range of 0.1 to 100 denier can be suitably used. The shape is also not particularly limited so long as it is fibrous, and examples thereof include a thin cylinder, a split yarn, a staple, a filament, and a web.

[0099] When the water-absorbent resin particles are used together with fibrous material to form an absorbent, the weight ratio of the water-absorbent resin particles to fibers (weight of water-absorbent resin particles / weight of fibrous material) is preferably 40 / 60 to 90 / 10, more preferably 70 / 30 to 80 / 20.

[0100] <Absorbent articles> The absorbent article can be obtained by using the water-absorbing resin composition. Specifically, the absorbent body is used. The absorbent article can be used not only for sanitary products such as paper diapers and sanitary napkins, but also for various applications such as dew condensation prevention agents, agricultural and horticultural water retention agents, waste blood solidification agents, disposable warmers, and the like, for absorbing and retaining various aqueous liquids in various industrial fields, and for gelling agents. The manufacturing method of the absorbent article is the same as that of the known one (described in JP-A-2003-225565, JP-A-2006-131767, JP-A-2005-097569, and the like). EXAMPLES

[0101] The present invention will be further described below with reference to examples and comparative examples, but the present invention is not limited thereto. Unless otherwise specified, parts refer to parts by weight. The water retention capacity, absorption rate by the vortex method, gel liquid permeation rate, and water absorption capacity under load of the water absorbent resin composition were measured in a room at 25±2°C and 50±5 RH% by the following methods. The temperature of the 0.9 wt% physiological saline solution used was adjusted to 25°C±2°C in advance.

[0102] <Method of measuring viscosity> A HARIO 200 mL tall beaker containing the measurement sample was placed in a thermostatic bath set to 25.0°C and left to stand until the sample temperature reached 25.0±0.5°C. After that, with the tall beaker containing the measurement sample still in the thermostatic bath, a TV-10M (manufactured by Toki Sangyo Co., Ltd.) was used to attach an M guard and M1 rotor and perform measurements at a rotation speed of 60 rpm. When the viscosity exceeded the measurable range, the rotation speed and the type of rotor were appropriately adjusted and the measurement was performed.

[0103] <Method of measuring water retention> 1.00 g of the water-absorbent resin composition was placed in a tea bag (20 cm long, 10 cm wide) made of nylon mesh with an opening of 63 μm (JIS Z8801-1:2006), and immersed in 1,000 ml of 0.9% by weight physiological saline for 1 hour without stirring, then pulled out and hung for 15 minutes to drain. After that, the tea bag was placed in a centrifuge and centrifuged at 150 G for 90 seconds to remove excess physiological saline, and the weight (h1) including the tea bag was measured, and the water retention capacity was calculated using the following formula. Water retention amount (g / g)=(h1)-(h2) In addition, (h2) is the weight of the tea bag measured in the same manner as above when no measurement sample is present.

[0104] <Absorption rate by vortex method> The water-absorbent resin composition was sieved into a range of 300 to 600 μm using a standard sieve to prepare a measurement sample. The time (unit: second) required for 2,000 g of the measurement sample to completely absorb 50 g of physiological saline solution stirred at 600 revolutions per minute in a 100 ml tall beaker with a flat bottom as specified in JIS R 3503 was measured in accordance with JIS K7224-1996, and this was taken as the absorption speed measured by the vortex method.

[0105] <Gel permeability rate> Measurement was performed using the device shown in Figs. 1 and 2 according to the following procedure. 0.32 g of the water absorbent resin composition sieved into the range of 300 to 600 μm using a standard sieve was immersed in 150 ml of physiological saline 1 (salt concentration: 0.9%) for 30 minutes to prepare swollen gel particles 2. Then, a vertically standing cylinder 3 {diameter (inner diameter) 25.4 mm, length 40 cm, graduation lines 4 and 5 are provided at the positions of 60 ml and 40 ml from the bottom, respectively. The prepared swollen gel particles 2 were transferred together with physiological saline into a cylindrical filtration tube having a wire mesh 6 (mesh size 106 μm, JIS Z8801-1:2006) and an openable / closable cock 7 (inner diameter of the liquid passage part 5 mm) at the bottom of the filtration tube, with the cock 7 closed, and then a pressure shaft 9 (weight 22 g, length 47 cm) with a circular wire mesh 8 (mesh size 150 μm, diameter 25 mm) bonded perpendicularly to the wire mesh surface was placed on the swollen gel particles 2 so that the wire mesh and the swollen gel particles were in contact with each other, and a weight 10 (88.5 g) was placed on the pressure shaft 9 and allowed to stand for 1 minute. The cock 7 was then opened, and the time (T1; seconds) required for the liquid level in the cylindrical filtration tube to reach the 40 ml graduation line 5 from the 60 ml graduation line 4 was measured, and the gel liquid passage speed (ml / min) was calculated from the following formula. Gel flow rate (ml / min) = 20ml x 60 / (T1-T2) The temperature of the physiological saline solution used and the measurement atmosphere was 25°C ± 2°C, and T2 was the time measured in the absence of a measurement sample by the same procedure as above.

[0106] <Absorption capacity under load> The water-absorbent resin composition was sieved into a range of 300 to 600 μm using a 30 mesh sieve and a 60 mesh sieve to prepare a measurement sample. 0.16 g of the measurement sample was weighed into a cylindrical plastic tube (inner diameter: 25 mm, height: 34 mm) with a nylon net with a mesh size of 63 μm (JIS Z8801-1: 2006) attached to the bottom, and the cylindrical plastic tube was vertically adjusted so that the measurement sample had a substantially uniform thickness on the nylon net, and then a weight (weight: 310.6 g, outer diameter: 24.5 mm) was placed on the measurement sample. After measuring the weight (M1) of the entire cylindrical plastic tube, the cylindrical plastic tube containing the measurement sample and the weight was vertically placed in a petri dish (diameter: 12 cm) containing 60 ml of physiological saline (salt concentration 0.9%), with the nylon net side facing down, and left to stand for 60 minutes. After 60 minutes, the cylindrical plastic tube was removed from the petri dish and tilted to collect the water adhering to the bottom in one place and drip it as droplets to remove excess water, and the total weight (M2) of the cylindrical plastic tube containing the measurement sample and weight was measured, and the absorption amount under pressure was calculated using the following formula. The temperature of the physiological saline solution and the measurement atmosphere was 25°C ± 2°C. Absorption amount under load (g / g)={(M2)-(M1)} / 0.16

[0107] <Example 1> 270 parts of acrylic acid (a1) {100% purity, manufactured by Mitsubishi Chemical}, 1.148 parts of internal crosslinking agent (b) {pentaerythritol triallyl ether, manufactured by Daiso}, and 716 parts of ion-exchanged water were stirred to obtain a mixture. While keeping the mixture at 3°C, nitrogen was introduced into the mixture to reduce the amount of dissolved oxygen to 1 ppm or less, and then 0.648 parts of a 1% aqueous hydrogen peroxide solution, 1.215 parts of a 2% aqueous ascorbic acid solution, and 9.45 parts of a 2% aqueous 2,2'-azobisamidinopropane dihydrochloride solution were added and mixed to initiate polymerization. After the temperature of the mixture reached 80°C, it was aged at 80±2°C for about 5 hours to obtain a hydrous gel.

[0108] Next, 315.56 parts of 48% potassium hydroxide aqueous solution was added to this hydrogel, and the mixture was placed in a mincer (12VR-400K manufactured by ROYAL) and chopped at a gel temperature of 80°C. 0.41 parts of sucrose stearate (Ryoto Sugar Ester S-370 manufactured by Mitsubishi Chemical Foods Corporation, HLB: 3) was added as a hydrophobic substance (c) and mixed to neutralize the hydrogel and mix the hydrophobic substance. The neutralized and mixed hydrogel was dried in a ventilation type dryer (manufactured by Inoue Metal Industry Co., Ltd.) under conditions of a supply temperature of 150°C and a wind speed of 2 m / sec for 30 minutes to obtain a dried product. The dried product was pulverized in a juicer mixer (OSTERIZER BLENDER manufactured by Oster), sieved, and adjusted to a particle size range of 710 to 150 μm in openings to obtain a crosslinked polymer (A-1).

[0109] While stirring 100 parts of the crosslinked polymer (A-1) at high speed (high-speed stirring turbulizer manufactured by Hosokawa Micron, rotation speed: 2000 rpm), 1.0 part of colloidal silica [Klebosol30cal25 (colloidal silica manufactured by Merck, solid content 30%)], 0.1 part of ethylene glycol diglycidyl ether as a surface crosslinking agent (c), 0.8 parts of ethylene glycol (viscosity at 25 ° C. = 21 mPa s) as a polyvalent hydroxyl group-containing compound (B), and 1.4 parts of water were mixed, and 3.3 parts of a surface crosslinking agent composition obtained by mixing 0.6 parts of sodium aluminum sulfate 12-hydrate, 0.8 parts of ethylene glycol (viscosity at 25 ° C. = 21 mPa s) as a polyvalent hydroxyl group-containing compound (B), and 1.7 parts of water were simultaneously added, and the mixture was uniformly mixed, and then heated at 130 ° C. for 30 minutes and cooled to room temperature to obtain a water absorbent resin composition (P-1).

[0110] <Example 2> A water absorbent resin composition (P-2) was obtained by the same operation as in Example 1, except that the ethylene glycol contained in each of the surface crosslinking agent composition and the mixed liquid was changed to propylene glycol (viscosity at 25°C = 48 mPa s).

[0111] <Example 3> A water absorbent resin composition (P-3) was obtained by the same operation as in Example 1, except that the ethylene glycol contained in each of the surface crosslinking agent composition and the mixed liquid in Example 1 was changed to 1,4-butanediol (viscosity at 25°C = 65 mPa s).

[0112] <Example 4> In Example 1, 315.56 parts of 48% potassium hydroxide aqueous solution was changed to 219.14 parts of 48% potassium hydroxide aqueous solution, and the ethylene glycol contained in each of the surface crosslinking agent composition and the mixed liquid was changed to propylene glycol, except that the same operation as in Example 1 was performed, to obtain a water absorbent resin composition (P-4).

[0113] <Example 5> In Example 1, 315.56 parts of 48% potassium hydroxide aqueous solution was changed to 394.45 parts of 48% potassium hydroxide aqueous solution, and the ethylene glycol contained in each of the surface crosslinking agent composition and the mixed liquid was changed to propylene glycol, except that the same operation as in Example 1 was performed to obtain a water absorbent resin composition (P-5).

[0114] <Example 6> In Example 1, 315.56 parts of 48% potassium hydroxide aqueous solution was changed to a mixture of 157.78 parts of 48% potassium hydroxide aqueous solution and 112.5 parts of 48% sodium hydroxide aqueous solution, 0.1 parts of ethylene glycol diglycidyl ether as a surface crosslinking agent (c) was changed to 0.12 parts, 0.8 parts of ethylene glycol contained in the surface crosslinking agent composition was changed to 1.0 parts of propylene glycol, 1.4 parts of water contained in the surface crosslinking agent composition was changed to 1.7 parts, 0.8 parts of ethylene glycol contained in the mixed solution was changed to 1.0 parts of propylene glycol, and 1.7 parts of water contained in the mixed solution was changed to 1.9 parts. Except for this, the same operation as in Example 1 was performed to obtain a water absorbent resin composition (P-6).

[0115] <Example 7> In Example 1, 0.41 parts of sucrose stearate as a hydrophobic substance (c) was changed to 0.54 parts of polyoxyethylene alkyl ether (Naroacty CL-40, HLB=9, manufactured by Sanyo Chemical Industries, Ltd.), and 0.8 parts of ethylene glycol contained in each of the surface crosslinking agent composition and the mixed liquid was changed to 0.8 parts of propylene glycol, except that the same operation as in Example 1 was performed, to obtain a water absorbent resin composition (P-7).

[0116] <Comparative Example 1> In Example 1, 315.56 parts of 48% potassium hydroxide aqueous solution was changed to 225.0 parts of 48% sodium hydroxide aqueous solution, 0.1 parts of ethylene glycol diglycidyl ether as a surface crosslinking agent (c) was changed to 0.15 parts, 0.8 parts of ethylene glycol contained in the surface crosslinking agent composition and the mixed liquid were changed to 1.1 parts of propylene glycol, 1.4 parts of water contained in the surface crosslinking agent composition was changed to 2.0 parts, and 1.7 parts of water contained in the mixed liquid was changed to 2.0 parts. Except for this, the same operation as in Example 1 was performed to obtain a comparative water absorbent resin composition (R-1).

[0117] <Comparative Example 2> A comparative water absorbent resin composition (R-2) was obtained by the same procedure as in Example 1, except that ethylene glycol, which is the polyhydric hydroxyl group-containing compound (B), was changed to glycerin (viscosity at 25°C = 950 mPa s).

[0118] The water-retaining capacity, the absorption rate by the vortex method, the gel permeation rate, and the water absorption capacity under load of the water-absorbent resin compositions (P-1) to (P-7) of Examples 1 to 7 and the comparative water-absorbent resin compositions (R-1) to (R-2) of Comparative Examples 1 to 2 were measured. The results are shown in Table 1.

[0119] [Table 1]

[0120] From the results shown in Table 1, it is understood that the water absorbent resin compositions of the present invention (Examples 1 to 7) have a high absorption rate by the vortex method, that is, a high SAP absorption rate, and further have excellent water retention and absorption under load. [Industrial Applicability]

[0121] The water-absorbent resin composition of the present invention can be applied to various absorbents to produce absorbent articles with a large amount of absorption and excellent return properties and surface dryness, and is therefore suitable for use in sanitary products such as paper diapers (such as paper diapers for children and paper diapers for adults), napkins (such as sanitary napkins), paper towels, pads (such as pads for incontinent people and underpads for surgery), and pet sheets (pet urine absorption sheets), and is particularly suitable for use in paper diapers. The water-absorbent resin composition of the present invention is useful not only for sanitary products, but also for various applications such as pet urine absorbents, urine gelling agents for portable toilets, freshness-preserving agents for fruits and vegetables, drip absorbents for meat and seafood, ice packs, disposable warmers, gelling agents for batteries, water-retaining agents for plants and soil, dew-preventing agents, waterproofing materials, packing materials, and artificial snow. [Explanation of symbols]

[0122] 1. Saline 2. Hydrogel particles 3. Cylinder 4 Scale mark at 60ml from the bottom 5 Scale mark at 40ml from the bottom 6. Wire Mesh 7. Cook 8 Circular Wire Mesh 9 Pressure shaft 10 Weight

Claims

1. A water-absorbent resin composition comprising a crosslinked polymer (A) having a structure in which a surface of the crosslinked polymer (A) is crosslinked with a surface crosslinking agent (c), the crosslinked polymer (A) having a constitutional unit derived from a potassium salt of a water-soluble unsaturated monocarboxylic acid (a1) and a constitutional unit derived from an internal crosslinking agent (b), A water-absorbing resin composition comprising a polyhydric hydroxyl group-containing compound (B) having a viscosity at 25°C of 20 to 100 mPa·s.

2. The water-absorbing resin composition according to claim 1, further comprising a hydrophobic substance (C).

3. An absorbent comprising the water-absorbent resin composition according to claim 1 or 2.

4. An absorbent article comprising the absorbent body according to claim 3.

5. A method for producing the water-absorbing resin composition according to claim 1 or 2, a polymerization step of polymerizing a monomer composition containing one or more monomers (A1) selected from the group consisting of water-soluble unsaturated monocarboxylic acids (a1) and their potassium salts, and monomers (a2) which become the water-soluble unsaturated monocarboxylic acids (a1) upon hydrolysis, and the internal crosslinking agent (b) to obtain a hydrogel containing the crosslinked polymer (A); A drying step of drying the hydrogel; and a surface crosslinking step of mixing a surface crosslinking agent composition containing the polyvalent hydroxyl group-containing compound (B) and the surface crosslinking agent (c) with the crosslinked polymer (A) and heating the mixture to surface crosslink the crosslinked polymer (A) with the surface crosslinking agent (c).

6. The method for producing a water absorbent resin composition according to claim 5, wherein the content of the polyvalent hydroxyl group-containing compound (B) in the surface crosslinking agent composition is 10% by weight or more and 60% by weight or less, and the content of the surface crosslinking agent (c) is 0.4% by weight or more and 5.0% by weight or less.

Citation Information

Patent Citations

  • Highly water-absorbable polymer composition

    JP1993086251A